The causes of bankruptcy among credit cardholders in Malaysia / Hafizuddin Noor Sa’ari - Noor Sa’ari, Hafizuddin (2013)
Nowadays, the number of bankruptcy is increase year by year. One of the serious bankruptcies in Malaysia is credit card bankruptcy. The aim of this research is to study or to examine the causes of credit card bankruptcy in Malaysia. In this research paper, the researcher chooses four independent variable that is consumer spending, interest rate, unemployment rate, and also inflation rate. Researcher use secondary data to complete this research paper and also use Microsoft excels and Statistical Program for Social Science (SPSS) to do the investigation and to get the result. In this research, all the independent variable is significant relationship with the dependent variable that is credit card bankruptcy. But three of the independent variable that is consumer spending, unemployment rate, and also inflation rate get negative relationship with the credit cards bankruptcy